El aprendizaje del álgebra escolar desde una perspectiva psicológica - Kieran, C.; Filloy Yagüe, Eugenio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper describes some of the main contributions of research to the growing knowledge of the cognitive processes which the learning of algebra in secondary schools involves. The continuous attempts of researchers to develop a theory on the teaching/learning of algebra are also discussed. Finally, some future trends in the teaching/learning of algebra are mentioned.